A multi-national validity analysis of the argumentativeness measure. Issue 1 (9th June 2020) - Croucher, Stephen Michael; Kelly, Stephanie; Burkey, Mark; Spencer, Anthony; Gomez, Oscar; Del Villar, Carmencita; Eskiçorapçı, Nadirabegim
Abstract : Purpose: The argumentativeness measure has been used in more than a 100 studies since 1982. The measure was developed and validated within a US university/college student sample. Despite its intended use, the measure is regularly used outside of the US and outside of the university/college setting without tests of validity. There is also intense debate as to the dimensionality of the measure, with one camp defending the bi-dimensionality of the measure and another proposing uni-dimensionality. Therefore, the purpose of this study was to assess the utility of the measure outside of its intended population. Design/methodology/approach: A total of seven samples were collected ( n = 1860) from the UK, Germany, France, Turkey, the Philippines, Nicaragua and the US. In this study, Infante and Rancer's (1982 ) original 20-item argumentativeness measure was used to assess argumentativeness. Confirmatory factor analyses was used to test content validity. Findings: Fit statistics were consistently poor for the unidimensional factor structure. As there is debate as to whether the measure is uni or bi-dimensional, a bi-dimensional fit was also analysed. The measure performed slightly better in each sample using a bi-dimensional factor structure. However, fit statistics were still poor for each sample. Research limitations/implications: Specifically, the seven samples are convenience samples. While such a sampling technique does limit the generalizability of a study's findings, convenience samples are common when using the argumentativeness measure. These results present avenues for exploring the dimensionality of the argumentativeness measure and for revisiting cross-cultural examinations of argumentativeness. Practical implications: Factor structure is a critical issue in validity. Whether authors specify their prediction or not, factor structure is always hypothesized as part of a study when measurements are used, and therefore, should be examined in every study as part of the scientific process. Making claims about human behaviour based upon measures with mis-specified factor structures or other validity issues can lead to the perpetuation of misinformation within the literature. Originality/value: This is one of the few studies to empirically explore the psychometric properties of one of the most used measures in argument/conflict research. In doing so, this study enhances the understanding of decades of argumentativeness research.